Beyond beliefs: an exploratory study of Division I athletic academic advisors’ social identity and professional beliefs about best practices for black male student-athletes - Moses, Ronald A. II (Kansas State University, 2019)
This dissertation will examine athletic academic advisors’ professional beliefs regarding academic challenges and preferred advising style for supporting the retention and matriculation of Black male student-athletes. Drawing on the key principles of intersectionality as a conceptual framework, I hypothesize that athletic academic advisors with shared social identities and similar past experiences will have also have similar perceptions of which advising style is best wen working with Black male student-athletes. A survey will be distributed to athletic academic advisors’ professional listservs and social media groups. Multinomial logistic regression test will be used to analyze multiple choice scale items, while open-ended items will be qualitatively coded. One goal is to help determine if differences in perception correspond to social groupings such as race, socioeconomic status or gender. These groupings are popular variables in research on athletic academic advising and athletic center cultures. A second goal is to explore if perceptions correspond to other, less studied group memberships such as political affiliation and athletic identity. A better understanding of athletic academic advisors’ identity and perceptions will be useful when developing practices to improve academic outcomes for Black male student-athletes.
Keywords: Athletic academic advisor; College athletics; Black male student; Student-athletes; Advising styles